Power, Identity, and Resistance in Maya Angelou’s Still I Rise: A Critical Discourse Analysis : https://doi.org/10.55966/assaj.2025.4.1.069 - Tariq Ullah; Dr. Shaukat Ali; Dr. Sajid Iqbal (`, 2025)
Language is not only utilized as a communication tool but also as an effective tool to construct identity, resist oppression, and exert social agency. Similarly, Poetry in literary fiction is an effective medium by which marginalized speech affirms resistance and recuperates narratives of dignity and empowerment. This research performs a Critical Discourse Analysis (CDA) of the poem Still I Rise by Maya Angelou, drawing on Norman Fairclough’s three-dimensional model to discuss how linguistic, rhetorical, and discursive resources generate themes of power, identity, and resistance. At the level of the text, the poem utilizes repetition, metaphor, lexical oppositions, and an assertive voice to represent a speaker who evinces self-value in opposition to racial and gender oppression. Through repeated words like "I rise," Angelou performs resilience and regains voice and agency for disempowered identities. On a discursive practice level, the poem subverts historical and institutional relations of power through direct address, rhetorical questioning, and intertextual allusion to slavery and institutional injustice, situating the speaker as a specific self and as a representative figure of collective resilience. Lastly, in the social practice sphere, Still I Rise is positioned within Black feminist scholarship and civil rights movements, counter-hegemonic to hegemonic discourse and delivering an alternative reading as one of ancestral pride and resistance. In this analysis, it is evident that Angelou’s poetry is not only literary but a discursive intervention which remakes Black womanhood and recovers cultural and political space. Keywords: CDA, Gender Oppression, Discursive Strategies, Poetry, Intertextuality